Effect of fractional carbon dioxide (CO2) laser on improving minoxidil delivery for treatment of androgenetic alopecia - Salah, Manal; Samy, Nevien; Mohamed Fawzy, Marwa; Farrag, Abdel Razik; Shehata, Hany; Hany, Aya (Journal of Lasers in Medical Sciences, 2020)
Introduction: Recently, laser treatment for hair loss has become very popular. Laser-assisted drug delivery (LAD) is an evolving technology with potentially broad clinical applications. This work aims at inspecting the effect of the fractional carbon dioxide laser (CO2) on improving the delivery of minoxidil in patients with androgenetic alopecia and detecting the role of the fractional CO2 laser in its treatment. Methods: We enrolled 45 Egyptians with male androgenetic alopecia (MAGA); clinical grading was assessed based on Norwood-Hamilton classification. The patients were divided into 3 groups: the first group (combined group) received the fractional CO2 laser session followed by topical application of minoxidil and also in between sessions; the second group received fractional CO2 laser sessions only and 6 sessions with 2-week intervals were performed; the third group applied topical minoxidil only for 3 months. Global photographs and dermoscopic assessments were performed before treatment and 3 months after the treatment. Results: Several dermoscopic findings were detected, including peripilar sign, hair diversity, yellow spot, white dots, and arborizing red lines. The number of double hair units significantly increased after the treatment in the combined group. The mean number of hair after the treatment in the 3 groups significantly increased, mostly in the combined group. The hair thickness (thin & thick) significantly increased after the treatment in the combined group and the fractional group; however, in the minoxidil group, only thin hair thickness increased. In all the 3 groups, there was a significant improvement in hair count and thickness. Conclusion: The ablative fractional CO2 laser alone or combined with minoxidil may serve as an additional treatment for MAGA.